2005
DOI: 10.1159/000084509
|View full text |Cite
|
Sign up to set email alerts
|

Invasion and Metastasis in Colorectal Cancer: Epithelial-Mesenchymal Transition, Mesenchymal-Epithelial Transition, Stem Cells and β-Catenin

Abstract: Invasion by colorectal carcinomas is characterized by an epithelial-mesenchymal transition (EMT)-like dedifferentiation of the tumor cells. However, a redifferentiation towards an epithelial phenotype, resembling a mesenchymal-epithelial transition, is detectable in metastases. This indicates that malignant progression is based on dynamic processes, which cannot be explained solely by irreversible genetic alterations, but must be additionally regulated by the tumor environment. The main oncoprotein in colorect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
414
1
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 497 publications
(443 citation statements)
references
References 97 publications
20
414
1
8
Order By: Relevance
“…These changes are similar to those observed in epithelial-mesenchymal transition at the advancing margin of other tumors, such as colorectal carcinoma. [12][13][14]22,23 Earlier, we have noted that areas of MELF-type invasion are strongly positive for CK7 and show reduced E-cadherin and hormone receptor expression. 20 These findings sometimes differed from those of the predominant conventional tumor areas, illustrating the importance of correlating the immunophenotypic findings with tumor distribution and morphology.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…These changes are similar to those observed in epithelial-mesenchymal transition at the advancing margin of other tumors, such as colorectal carcinoma. [12][13][14]22,23 Earlier, we have noted that areas of MELF-type invasion are strongly positive for CK7 and show reduced E-cadherin and hormone receptor expression. 20 These findings sometimes differed from those of the predominant conventional tumor areas, illustrating the importance of correlating the immunophenotypic findings with tumor distribution and morphology.…”
Section: Discussionmentioning
confidence: 90%
“…19,20 Expression of cyclin D1 in MELF areas would also be consistent with epithelial-mesenchymal transition as cyclin D1 is characteristically upregulated during this process in other types of carcinoma. [12][13][14]22,23 Abnormalities of b-catenin have also been shown in a significant proportion of endometrial neoplasms. 3,5 Mutations have been recorded in 13-31% cases and appear more common in lowgrade endometrioid adenocarcinomas, [31][32][33][34][35][36] whereas an abnormal immunolocalization in the form of reduced membrane staining with diffuse cytoplasmic and/or nuclear staining has been recorded in 25-76% cases.…”
Section: Endometrial Carcinoma Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…An intracellular accumulation of the g2 (and b3) subunit(s) is found at the invasive fronts of some colorectal cancers and in particular in budding cancer cells; however, no a3 expression can be detected at these sites (Sordat et al, 2000). This pattern of laminin-5 g2 (and b3) expression apparently is not the direct consequence of genetic alterations, rather it is interpreted as a response of the genetically altered tumor cells to stromal signals active at the invasion fronts (Brabletz et al, 2005). Whereas LAMC2 has been characterized as a b-catenin target gene (Hlubek et al, 2001), activation of the Wnt/ b-catenin pathway on its own is not sufficient to perturb balanced expression of the laminin-5 heterotrimer as shown with adenoma cells in vitro and in vivo (Sordat et al, 2000).…”
Section: Discussionmentioning
confidence: 97%
“…Wnt signaling regulates various functions of the cancer cell such as proliferation, cell fate decision, motility and invasion through activating β‐catenin (Clevers, 2006). A large body of evidences have suggested that the canonical Wnt/β‐catenin pathway plays an important role in inducing epithelial cancer cells to undergo epithelial–mesenchymal transition (EMT; Brabletz et al ., 2005; Taki et al ., 2003), which facilitates migration through the extracellular matrix and distant metastasis.…”
Section: Introductionmentioning
confidence: 99%